Threats and promises : the pursuit of international influence - Davis, James W., 1963- (Johns Hopkins University Press, 2000)
Conventional wisdom dictates that the conditions of international politics require states to pursue "tough" strategies based on threats, ruling out "soft" strategies such as reassurances or appeasement. In Threats and Promises, James W. Davis, Jr., works toward a theory of influence in international politics that recognizes the power of promises and assurances as tools of statecraft.Davis offers an analytic treatment of promises and assurances, drawing on relevant strands of international relations theory and deterrence theory, as well as cognitive and social psychology. Building on prospect theory (from cognitive psychology), he develops a testable theory of influence that suggests promises are most effective when potential aggressors are motivated by a desire to avoid loss. Davis then considers a series of case studies drawn principally from German diplomatic relations in the later nineteenth and early twentieth century. From the case studies -- which focus on such issues as European stability, colonial competition, and the outbreak of the First World War -- Davis shows how a blending of threats and promises according to reasoned principles can lead to a new system of more creative statecraft.While many critical analyses exist on the use of threats, there are relatively few on the use of promises. Davis argues that promises have been central to outcomes that were previously attributed to the successful use of deterrent threats, as well as the resolution of many crises where threats failed to deter aggression. Threats and Promises challenges the conventional wisdom, and is an original contribution to the field of international politics.